The Study of Plasma Activated Water Treatment for Microorganism in Soil - Millin, Arthur Marren; Mohd Razi, Rusyaidi Jazmiey; Ahmad Faiz Mat Zian @ Mat Zin; Roslan, Muhammad Sufi (Multidisciplinary Applied Research and Innovation, 2023)
In order to grow and develop, plants need food, just like all other living things. Plants require sixteen essential elements. Carbon, hydrogen, and oxygen are all found in the atmosphere and in soil water. The remaining 13 elements which are nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, iron, zinc, manganese, copper, boron, molybdenum, and chlorine are either supplied by soil minerals and soil organic matter or by organic or inorganic fertilizers. Thus, to increase the quality and growth rate of crops, farmers will use fertilizers. However, the usage of excess fertilizers lead to soil pollution and water pollution due to leaching of chemicals. With the usage of Plasma Activated Water (PAW), nutrients can be supplied to crops more organically and produce much less harm. PAW is also a good medium to stimulate the growth of nitrogen fixation bacteria, nitrobacter, which is important in supplying continuous dissolved nitrogen to plants. PAW contain various gaseous reactive species like OH, H2O2, NO and HNO as the result of plasma contact with the water surface. This study is being carried out by treating different distilled water samples with different times of plasma treatment to find the optimal time of treatment. The treated water is then poured to microorganisms in soil to check whether it can stimulate the growth of microorganisms that boost plant growth. The significance of this study is to increase the nutrient quality of the soils without using any chemicals such as fertilizer as well to improve the nitrogen fixation process for plants. To summarize, the plasma treated water contains a high amount of N=O bond which also shows the presence of nitrite ion and the plasma treated water also enhances the growth of microorganism in soil. Therefore, this study is successful since the relation with objectives is met